Glacial‐interglacial variability in diatom abundance and valve size: Implications for Southern Ocean paleoceanography. (16th October 2015) - Nair, Abhilash; Mohan, Rahul; Manoj, M. C.; Thamban, Meloth
Abstract: Antarctic sea ice extent along with Southern Ocean biological productivity varied considerably during glacial‐interglacial periods, and both are known to have played a considerable role in regulating atmospheric CO2 variations in the past. Here we present data on diatom absolute abundance (valves/g of sediment) and size over the past ~ 42 ka B.P. and how they link to glacial‐interglacial changes in Antarctic sea ice extent, Southern Ocean frontal systems, and aeolian dust flux. Our records of sea ice and permanent open ocean zone diatom abundances suggest a shift in the Antarctic winter sea ice limit and Polar Front respectively up to the modern‐day Polar Frontal Zone during marine isotopic stages (MIS) 2 and late MIS 3. In addition to glacial shifts in the Polar Front, diatom assemblages also recorded a plausible northward shifts in Polar Front during few intervals of MIS 1. Glacial periods north of the Polar Front in the Indian sector of the Southern Ocean were characterized by higher total diatom abundance, larger Fragilariopsis kerguelensis apical length, and Thalassiosira lentiginosa radius. This is probably a consequence of (1) a northward expansion of the opal belt, a region characterized by high production and export of biogenic silica; (2) an increase in terrigenous input, via erosion of Crozet Islands; and (3) the alleviation of iron deficit by high input of Fe‐bearing dust. The larger and highly silicified diatoms such as F . kerguelensis and T . lentiginosa may have mainly contributed in transporting biogenic silica and organic carbon to the seabed for the last 42 ka, in the northern Polar Frontal Zone of the Indian sector of the Southern Ocean. Key Points: Glacial rise in diatom abundance and size, Indian Ocean sector of Southern Ocean Shift of Antarctic sea ice limit and frontal systems during the glacial Period Changes in ocean process control the variation in diatom abundance and size